Investigation of the mechanical behaviour of an unsaturated soil mixture using a digital image measurement system. Issue 8 (2nd July 2020) - Zheng, Guofeng; Shao, Longtan; Guo, Xiaoxia; Zhang, Junda
Abstract: A triaxial apparatus that includes a digital image measurement system (DIMS) is used to investigate the mechanical behaviour of a compacted soil mixture of tailing sand and speswhite kaolin. The experimental programme involves a series of soil–water retention curve (SWRC) tests, isotropic compression tests and suction-controlled triaxial tests. A non-contact method for measuring the sample volume is developed based on the strain field obtained from the DIMS. Particular attention is given to the volumetric behaviour of the soil, and three distinct stages are observed during the consolidation of the suction-controlled triaxial tests. Then a void ratio-dependent shear strength model is proposed, incorporating the influence of the change in void ratio on the SWRC pattern. The model is validated against the experimental data from the tests, showing that it can provide a more accurate prediction of shear strength than that of conventional predictions using a unique SWRC. Moreover, the proposed model is capable of representing several important aspects of the shear behaviour of unsaturated soils, such as the dependence of suction-induced strength on net normal stress and density effect on the shear strength.